Pengaruh Custmer Relationship Management (CRM) Dan Kepercayaan Terhadap Loyalitas Nasabah Di Bank Permata Syariah Kota Jambi - Ryan Akbar (JOURNAL SAINS STUDENT RESEARCH, 2023)
This study aims to examine the effect of customer relationship management (CRM) and trust on customer loyalty at Permata Syariah Bank, Jambi City. The sampling technique used is the Slovin formula. The sample used is the customer at Permata Syariah Bank, Jambi City. Based on the slovin formula method, there were 90 customers at Permata Syariah Bank Jambi City who met the criteria. The results of this study indicate that partially the Customer Relationship Management and trust variables have a significant effect on customer loyalty at Bank Permata Syariah. The Customer Relationship Management variable has a significant effect on Bank Permata Syariah customer loyalty. The trust variable has a significant effect on Bank Permata Syariah customer loyalty.